Organização espacial da produção de erva-mate no município de Palmitos/SC - Moraes, Cristina de (2010)
This study aims to understand the relation between the spatial organization of Palmitos / SC and production of yerba mate, over time. The exploitation of this natural resource is linked with the earliest forms of human occupation in space developed which includes the city under study. During this period played main role in determining the ways that space received from human action. Concomitantly, it is this same period that have intensified the disputes between Brazil and Argentina for that space, in a diplomatic row nominated as Question of Palmas. After the resolution of this, the Brazilian government's policies with territorial immigration geoeconomic and geopolitical interests, as evidenced by the deployment of small farms, which no strength to produce the export products to turn their production to grocery, absorbed by the demand generated by urbanization and industrialization developed in southeastern Brazil. In this context, the exploitation of mate takes a secondary role in this socio-spatial formation, in which cereal production and livestock development, especially pigs, have assumed crucial role in determining the region's economy and spatial organization. After the restructuring of production in the 1970s, in which the industry ervateira experiencing a technical improvement that increases the demand for raw material, is contributing to upgrading the product. Moreover, through the same phenomenon (restructuring productive) farmers experience a process of selectivity and marginalization, which induces the constant search for alternative production enabled the social reproduction of the same. The combination of these factors corresponds to the assumptions that account for the reintegration of the cultivation of yerba mate in the city, with high production of this statement in 1996 (Agricultural Census, 1996). To perform the study, it became necessary to understand historical and geographical formations of space developed in Palmitos / SC ervateira and peculiarities of the activity.